Aplikasi SMS Gateway untuk Mahasiswa sebagai Info on Demand - PURNAMA, Adhitya Oktora ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This report is intended to outline the SMS Application Gateway for Students For Info On Demand, describing how the system works and excellence in providing academic information to students. Preparation of this paper begins by extracting ideas and creativity continued development literature that supported the consultation to faculty then performed data collection and information. Making this report directed by the supervisor. The system proposed in this report is the SMS Gateway Application for Student For Info On Demand. This system begins with identifying the needs of student academic information can be accessed via SMS and with any CellPhone. If students want to get the student's academic information must first enroll in the academic (user) password by including information about the student that is not known by other students. Thus students just type SMS format provided by the user in order to access the required information. SMS Gateway application for Students For Info On Demand is expected to be a product that is easily accessible and inexpensive that can also help students in getting information from academic and academic authorities can also easily give information to students more efficiently.